Future-relevant memories are not selectively strengthened during sleep - Jennifer E. Ashton (Public Library of Science (PLoS), 2021)
Overnight consolidation processes are thought to operate in a selective manner, such that important (i.e. future-relevant) memories are strengthened ahead of irrelevant information. Using an online protocol, we sought to replicate the seminal finding that the memory benefits of sleep are enhanced when people expect a future test [Wilhelm et al., 2011]. Participants memorised verbal paired associates to a criterion of 60 percent (Experiment 1) or 40 percent correct (Experiment 2) before a 12-hour delay containing overnight sleep (sleep group) or daytime wakefulness (wake group). Critically, half of the participants were informed that they would be tested again the following day, whereas the other half were told that they would carry out a different set of tasks. We observed a robust memory benefit of overnight consolidation, with the sleep group outperforming the wake group in both experiments. However, knowledge of an upcoming test had no impact on sleep-associated consolidation in either experiment, suggesting that overnight memory processes were not enhanced for future-relevant information. These findings, together with other failed replication attempts, show that sleep does not provide selective support to memories that are deemed relevant for the future.